(untitled) (Research, Society and Development, 2023)
The Burnout Syndrome is a phenomenon psychosocial characterized by the exhaustion of workers due to coping with the stressors present in a work space. The workers affected have physical and emotional symptoms like irritability, changes in concentration, sleep disorders and muscle aches, and since the areas of health and education are in direct contact with society, these are the professionals most affected by Burnout. The purpose of this study was to identify the prevalence of Burnout in higher education teachers who work as health professionals, and simultaneously, work as professors in a university in the capital of northeast Brazil. A cross-sectional epidemiological study was conducted with 64 professors from a public health university, through an electronic sociodemographic questionnaire sent to the participants and the Maslach Burnout Inventory (MBI) to assess Burnout Syndrome. The results Indicate the absence of Burnout Syndrome within the population studied, regarding that there are was a higher profissional achievement among the participants. Although there is an absence of Burnout in the population, understand the high values of emotional exhaustion and depersonalization as preceptors of illness in this population.